PENGARUH STATUS SOSIAL EKONOMI MASYARAKAT KOTA DENPASAR TERHADAP PEMILIHAN TRANS SARBAGITA SEBAGAI MODA TRANSPORTASI (STUDI di KORIDOR I dan II) - Margareth Sihotang, Deasy Event; Tamim, Imron Hadi; Astika, Ketut Sudhana (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT This research is motivated by the presence of Trans Sarbagita which have an impact in the daily life of people in Denpasar. Trans Sarbagita is a government-owned public transport by Bali Province is enough to attract attention, especially the people of Denpasar. Different level of socioeconomic status Denpasar becomes interesting when linked with the use of Trans Sarbagita as a mode of daily transportation. Therefore, this study aimed to determine whether or not the influence of socioeconomic status of people in Denpasar with the selection Sarbagita TransÂ  as a mode of transportation. Theory that used in this research is social stratification. This study used quantitative research methods using non-probability sampling technique to 100 respondents that people in Denpasar as Trans users Sarbagita corridor I and II. Based on the occupation, the use of Trans Sarbagita dominated with lower socioeconomic status with an average job such as students, drivers, workers, retirees and housewives. Based on the latest education, the use of Trans Sarbagita dominated by people in Denpasar with a moderate level of socioeconomic status with an average of the last education is high school, while based on income, use of Trans Sarbagita dominated by low socioeconomic status levels with an average income below Rp 1.500.000, -. Judging from the frequency of use Trans Sarbagita in a week, the level of socioeconomic status (employment, education, income) does not affect the election of Trans Sarbagita as a mode of transportation. Keywords: Effects, Socio-Economic Status, election mode of transportation, Trans Sarbagita.